Expert Answers
pohnpei397 eNotes educator| Certified Educator

The first step is to try to isolate the x term on the left.

One way to do this is to subtract 2/3 from each side.

Now we have -7/3x = 17.333

Now we multiply both sides by 3x.  That gives us

-7 = 52x

Now we divide both sides by 52.

x = -7/52

 

You can get the same result by multiplying both sides by 3x as the first step in solving the equation.

That gives you

-7 + 2x = 54x

Subtract 2x from each side and you have

-7 = 52x

x = -7/52

dondoomdondoom | Student

-7+2x= 3x.18

-7+18= 3x-2x

11=x

neela | Student

-7/3x+2/3 =18

-7/3x  equals -2.333x , as division and multiplication are of equal preference. but division is first as it comes first. With this angle we proceed. We treat -7/3x or -7  /3x diffrent from 7/(3x).

To solve this we multiply both sides by 3 to get away with the denominator.

-7x+2=18*3. Or

-7x+2-2 = 54-2 . Subtracted 2 from both sides.

-7x= 52.

x = 52/(-7) . Divided by -7 both sides.

=(7+3/7) = -7.428571...

giorgiana1976 | Student

-7/3x+2/3=18

First, let's make all ratios to have the same denominator, which is 3x.

For this reason, we'll multiply by x the ratio 2/3 and also, we'll multiply by 3x, to the right side of the equation.

The equation will have the following form:

-7 + 2x = 18*3x

-54x + 2x = 7

-52x=7

x = -7/52

krishna-agrawala | Student

Given:

-7/3x + 2/3 = 18

Multiplying both sides by 3x we get:

3x*(-7/3x) + 3x*2/3 = 3x*18

-7 + 2x = 54x

54x - 2x = -7

52x = -7

Therefore:

x = -7/52